Produktivitas Tenaga Kerja Pada Pekerjaan Kolom (Studi Kasus : Proyek Pembangunan Gedung Education Center Fakultas Ilmu Sosial Dan Ilmu Politik Tahap I Universitas Hasanuddin) - Riski Christian Lumombang; Junus Mara; Ari Kusuma (Paulus Civil Engineering Journal, 2023)
The success of a job in a construction project is inseparable from the presence of labor. In its implementation, the level of labor productivity is very important in order to provide maximum results. In the construction project of the education center building, faculty of social and political sciences phase 1 of Hasanuddin University, research was carried out with the aim of determining labor productivity, especially in ironing and column formwork. This research was conducted using a descriptive analysis method, namely a direct survey in the field to obtain labor productivity in ironing and column formwork after that compared with SNI 7394 – 2008. From the results of the analysis of labor productivity in ironing and column formwork work, the average productivity value of artisans for column ironing work is 164.585 kg / person / day while column formwork work is 5.748 m2 / person / day. For productivity based on SNI, the productivity of column ironing work was 142,857 kg / person / day while column formwork was 3,030 m2 / person / day.